Research note. A CMOS cell for parallelly loadable counters - Kulaib, Munir Ahmed (1987)
A CMOS flip-flop cell which can be used in counters is designed. SPICE model, the transient response and the CMOS layout are presented. When used in counters, the flip-flop can be loaded to initialize the count.